Multimodal analgesia for craniotomy. Issue 5 (October 2019) - Ban, Vin Shen; Bhoja, Ravi; McDonagh, David L.
Abstract : Purpose of review: To explore the data for and against the use of the various components of multimodal analgesia in cranial neurosurgery. Recent findings: Postcraniotomy pain is a challenging clinical problem in that analgesia must be accomplished without affecting neurologic function (i.e. 'losing the neurologic exam'). The traditional approach with low-dose opioids is often insufficient and can cause well recognized side effects. Newer multimodal analgesic approaches have proven beneficial in a variety of other surgical patient populations. The combined use of multiple nonopioid analgesics offers the promise of improved pain control and reduced opioid administration, while preserving the clinical neurologic exam. Specifically, acetaminophen and gabapentinoids should be considered for craniotomy patients, both preoperatively and postoperatively. The gabapentinoids have the added benefit of reduced nausea. Scalp blocks have moderate quality evidence supporting their use over incisional infiltration alone, with analgesia that extends into the postoperative period. Intraoperative dexmedetomidine reduces postoperative opioid requirements with the added benefit of reduced postcraniotomy hypertension. Methocarbamol, NSAIDs [both nonspecific cyclooxygenase (COX) 1 and 2 inhibitors and specific COX-2 inhibitors], ketamine, and intravenous lidocaine require further data regarding safety and efficacy in craniotomy patients. Summary: Opioids are the mainstay for treating acute postcraniotomy pain but should be minimized. The evidence to support a multimodal approach is growing; neuroanesthesiologists and neurosurgeons should seek to incorporate multimodal analgesia into the perioperative care of craniotomy patients. Preoperative and postoperative gabapentin and acetaminophen, intraoperative dexmedetomidine, and scalp blocks over incisional infiltration have the most data for benefit, with good safety profiles. Further research is needed to define the safety, efficacy, and dosing parameters for NSAIDs including COX-2 inhibitors, methocarbamol, ketamine, and intravenous lidocaine in cranial neurosurgery.